Mainstreaming Gender Equality in Family Planning: A Case Study of the Vasectomy Program in Surabaya - Nofitasari, Nofitasari; Efendi, Agus Syaifudin; Prakasita, Ajeng Widya (Journal Politique, 2025)
This article explores the inconsistency in how gender mainstreaming policies are applied within the Family Planning (KB) program in Surabaya, where these policies still impose structural burdens on women. The low vasectomy rate (0.31%) amid widespread contraceptive use highlights the state's challenge in addressing the patriarchal structures and male dominance in society. Using a qualitative case study approach, this research assesses the Surabaya City Government's capacity to reformulate its intervention strategies on the vasectomy program. Findings indicate that the program's success largely depends on shifting from policy tools focused on providing medical facilities to those targeting cultural change. The effectiveness of informal networks in male public spaces, along with strong political support from regional leaders, has helped reduce resistance rooted in fears of emasculation. This study argues that attaining reproductive justice requires transforming governance to be more responsive and positioning vasectomy as a strategic policy tool to challenge gender inequalities.